SISTEM PENDUKUNG KEPUTUSAN PESERTA KB TELADAN DI BKKBN BENGKULU MENGGUNAKAN PEMROGRAMAN VISUAL BASIC 6.0 - Yulianti, Liza; Sari, Herlina Latipa; Haryadi, B Herawan (Jurnal Media Infotama, 2012)
Problem of which often happened in course of determining family planning (KB) example among others is decision making su1)bjectivity, especially if some existing family planning (KB) niner have value or ability which [do] not far differ. Usage of System Supporter Decision, expected to lessen subjectivity in decision makingSystem Supporter Decision by using this gap analysis is made pursuant to norm and code - human resource norm. Peruses Enumeration of gap conducted to determine employees recommendation in system election of family planning (KB) example pursuant to criteria some which have been determined by side which assessing.Result of from this process in the form of wight assessment of family planning (KB) example. This competent assessment become of family planning (KB) example participant in BKKBN Bengkulu. This Software is made with Microsoft Access applying for 2003 and is Visual Basic 6.0. as tool.